Examination of in situ and ex situ catalytic fast pyrolysis and liquid fractionation utilizing a free-fall reactor - Struhs, Ethan; Mirkouei, Amin; Appiah, Harrison; McDonald, Armando G. (Frontiers in Industrial Microbiology, 2024)
This study examines biomass valorization through thermochemical conversion by an integrated catalytic fast pyrolysis process with liquid fractionation using a free-fall reactor, γ-alumina, as a catalyst and methanol for direct quenching. The novelty lies within the process intensification (i.e., a single-step conversion and fractionation pathway) to improve pyrolysis oil yield and quality. In particular, the conversion bioprocess utilizes in situ or ex situ catalytic free-fall fast pyrolysis reactors at 550°C and 10–15 psi to produce pyrolysis oil and char (bio-oil and biochar) from pinewood feedstocks. The results from the gas chromatography–mass spectrometry show that the main volatile fractions of bio-oil compounds are levoglucosan, furfural, hydroxy acetone, methyl acetate, and catechol. The electrospray ionization–mass spectrometry results determine the average molar mass, revealing improved cracking, thermal treatment, and fraction stabilization. The Fourier transform infrared spectroscopy and thermal aging provide insight into the change in functional groups in relation to experimental parameters. The outcomes indicate that γ-alumina successfully decreased acidic compounds and increased esters and phenolic content in the bio-oil. The bio-oil produced from the ex situ catalytic pyrolysis also shows the highest liquid yield (~41%), high phenolic content, and thermally stable properties. The in situ catalytic pyrolysis exhibits lower yields but favors high ketone formation. Fractions condensed in methanol exhibit the highest thermal stability and esterification potential; however, they still possess relatively high amounts of acidic compounds. It is concluded that ex situ catalytic pyrolysis, using γ-alumina catalyst and fractionation with methanol, can improve conversion reactions, particularly bio-oil quality, yield, and thermal stability.